Phase-Related Changes in the Sirtuin 1–High Mobility Group Box 1 Axis and Nicotinamide Adenine Dinucleotide in Ischemic Stroke - Bai, Lingling; Kang, Tao (Journal of Medical Biochemistry, 2026)
Background: This study investigated phase-related (acute, subacute, and recovery phases) changes in the peripheral blood sirtuin 1 (SIRT1)-high mobility group box 1 (HMGB1) axis after ischemic stroke (IS) and evaluated agreement between enzyme-linked immunosorbent assay and high-performance liquid chromatography for serum nicotinamide adenine dinucleotide (NAD+) measurement.Methods: Eighty patients with IS were classified as acute, subacute, or recovery phase according to time from onset, and 40 age- and sex-matched controls were included. Serum SIRT1, HMGB1, acetylated HMGB1, NAD+, interleukin-1 beta, tumor necrosis factor-alpha, and interleukin-10 were measured. Peripheral blood expression of SIRT1, HMGB1, inducible nitric oxide synthase, and arginase-1 messenger RNA was determined. Agreement for NAD+ measurement was assessed by Bland-Altman analysis.Results: In the acute phase, serum SIRT1 and NAD+ were lowest, whereas HMGB1, acetylated HMGB1, proinflammatory cytokines, and the inducible nitric oxide synthase/arginase-1 ratio were highest (P